Unravelling Structural Dynamics within a Photoswitchable Single Peptide: A Step Towards Multimodal Bioinspired Nanodevices. Issue 50 (12th October 2020) - Chen, Xinjiani; Yeoh, Yuan Qi; He, Yanbin; Zhou, Chenguang; Horsley, John R.; Abell, Andrew D.; Yu, Jingxian; Guo, Xuefeng
Abstract: The majority of the protein structures have been elucidated under equilibrium conditions. The aim herein is to provide a better understanding of the dynamic behavior inherent to proteins by fabricating a label‐free nanodevice comprising a single‐peptide junction to measure real‐time conductance, from which their structural dynamic behavior can be inferred. This device contains an azobenzene photoswitch for interconversion between a well‐defined cis, and disordered trans isomer. Real‐time conductance measurements revealed three distinct states for each isomer, with molecular dynamics simulations showing each state corresponds to a specific range of hydrogen bond lengths within the cis isomer, and specific dihedral angles in the trans isomer. These insights into the structural dynamic behavior of peptides may rationally extend to proteins. Also demonstrated is the capacity to modulate conductance which advances the design and development of bioinspired electronic nanodevices. Abstract : Reported is a single‐molecule junction containing a single peptide with an azobenzene photoswitch to interconvert between the trans (left) and cis (right) configurations upon photoisomerization using UV and visible light. Real‐time electrical measurements revealed multimodal conductance states within each isomer, providing insights into the structural dynamics, and demonstrated the capacity to modulate conductance for bioinspired electronic nanodevices.